Evaluating the Performance of Arabic Language Teachers in the Light of Applying the Comprehensive Quality Standards According to the Professional Supervisors - Rahima, Farman Qaht (International Journal of Psychosocial Rehabilitation, 2020)
Educational views increased calling for the necessity of developing, training and qualifying teachers in line with the requirements of the times and keeping pace with scientific and technical progress to develop their performance in the light of comprehensive quality standards. Therefore, the current research aims at evaluating the performance of teachers of the Arabic language in the light of the application of comprehensive quality standards according to the professional supervisors and providing comprehensive quality standards to gain the performance skills of teachers. The first chapter concerns itself with the problem of research, its importance, then the goal of research and defining some terms. In the second chapter, a theoretical framework was presented in which it contains more than one dimension, in addition to a set of studies. In the third chapter, the researcher adopted the descriptive approach. As for the research community, it was represented by teachers of secondary and middle schools in the general directorates of education in the governorate of Baghdad. There are (6) six general directorates, as the number of teachers in these directorates reaches (5637) teachers and schools for the Arabic language. The researcher chose one of the general directorates to represent the main sample of the current research, as the third Directorate of Education in Al-Rusafa was chosen randomly. The number of individuals in the research sample reached (20) teachers and schools for the Arabic language from different education schools, and nine of the specialized supervisors. As for the research tool, it adopted a form counted with a group of experts from the Ministry of Education, and it applied it to teachers by supervisors at the appointed time. Then, he emptied its data using the appropriate statistical means, and this is what was presented in the fourth chapter of the research results, which seemed clear, which is the lack of teachers’ culture in the field of quality and its standards, and some indicators of the standards have shown at the expense of other indicators of the standards that have been prepared.